2004
DOI: 10.1007/s00330-004-2285-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution dental magnetic resonance imaging of inferior alveolar nerve responses to the extraction of third molars

Abstract: The objective of this study was to assess whether signal changes can be detected in the neurovascular bundle of the mandibular canal after the extraction of a third molar. We retrospectively analyzed MRI scans of 30 test subjects with healthy mandibles and 41 patients who had had a wisdom tooth extracted. Signal intensities were measured at particular sites in the neurovascular bundle, which were defined as regions of interest (ROI) in the sagittal T1-weighted images before and after intravenous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…[7][8][9] While on the other hand, the IAN was evaluated quantitatively using DTI and was visualized three-dimensionally by tractography in the present study. DTI can provide quantitative data based on the diffusivity and anisotropy of microscopic water motion within nerve fibres, and the nerve fibres can be visualized three-dimensionally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] While on the other hand, the IAN was evaluated quantitatively using DTI and was visualized three-dimensionally by tractography in the present study. DTI can provide quantitative data based on the diffusivity and anisotropy of microscopic water motion within nerve fibres, and the nerve fibres can be visualized three-dimensionally.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have evaluated the mandibular canal using MRI. [7][8][9] Among these, some researchers reported that changes to the neurovascular bundle including IAN could be evaluated on the basis of T 1 -and T 2 -related signal intensities on high-quality MR images.…”
Section: Introductionmentioning
confidence: 99%
“…These highresolution magnetic resonance sequences make it possible to analyze cranial nerves quantitatively for the first time [14,15]. In contrast to patients with acute inflammatory diseases of the cranial nerves (facial and inferior alveolar nerves) [16,17], patients with trigeminal neuralgia show no contrast enhancement of the affected region prior to surgery. The significant volume difference that was preoperatively noted between the affected and the healthy side in patients with neuralgia is, however, indicative of nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…All data presented in this study were acquired on a high-field (3 T) whole-body clinical MR system. The likely drop in SNR may be addressed e. g. by usage of intraoral-coils [34], surface coils [37], or even dedicated dental phased-array coils [53]. The high imaging costs and long acquisition times still likely restrict the application of MRI to clinical research.…”
mentioning
confidence: 99%